2005
DOI: 10.1254/jphs.fp0040525
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibitors Protect Against Degeneration of Nigral Dopaminergic Neurons in Hemiparkinsonian Rats

Abstract: Abstract. Parkinson's disease is characterized by dopaminergic neuronal death and the presence of Lewy bodies in the substantia nigra pars compacta (SNpc). a -Synuclein and ubiquitin are components of Lewy bodies, but the process of Lewy body formation and the relationship between inclusion formation and dopaminergic neuronal death have not been resolved. In this study, unilateral intranigral microinjection of 6-hydroxydopamine caused a significant loss of tyrosine hydroxylase-immunopositive neurons in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Furthermore, low-level of PSI exposure to SH-SY5Y cells was protective against serum withdrawal and oxidative stress (44). Together with the results by Inden et al (28) and Sawada et al (32) using PSI at low doses, the recent publications give us a cue to refine the link between UPS and the mechanisms of DA cell death. The effect of UPS inhibition might be harmful or beneficial, depending on the level of inhibition and other factors involved in DA cell maintenance.…”
mentioning
confidence: 60%
“…Furthermore, low-level of PSI exposure to SH-SY5Y cells was protective against serum withdrawal and oxidative stress (44). Together with the results by Inden et al (28) and Sawada et al (32) using PSI at low doses, the recent publications give us a cue to refine the link between UPS and the mechanisms of DA cell death. The effect of UPS inhibition might be harmful or beneficial, depending on the level of inhibition and other factors involved in DA cell maintenance.…”
mentioning
confidence: 60%
“…Although in vitro studies have found that UPS inhibitors can cause dopamine cell death, there has been a lack of data indicating that systemic treatment with UPS inhibitors alone causes specific dopamine neuron toxicity. In sharp contrast to in vitro studies, Inden et al (2005) suggested that proteasomal inhibition may afford protection against 6-hydroxydopamine-induced SN cell loss, suggesting that the role of proteasomal inhibition in dopamine cell loss is likely to be more complex than initially envisioned (see Setsuie et al, 2005). …”
Section: Discussionmentioning
confidence: 93%
“…Microscopically, proteinacious inclusions, termed "Lewy bodies" (LBs) are frequently detected in remaining nigral neurons of postmortem PD brains. The presence of these cytoplasmatic inclusions might be cytotoxic (Hurtig et al, 2000;Giasson et al, 2002;Braak et al, 2004), but there is increasing evidence that, in contrast, they might be cytoprotective by sequestering toxic protein structures (Gispert et al, 2003;Tanaka et al, 2004;Inden et al, 2005;Bodner et al, 2006). ␣-Synuclein (␣-syn) was identified as the major filamentous component of LBs (Spillantini et al, 1998).…”
Section: Introductionmentioning
confidence: 99%